Matrix stimulation in cancer pain: Methodology, safety and effectiveness. (14th August 2017) - Mücke, M.; Tils, M.; Conrad, R.; Kravchenko, D.; Cuhls, H.; Radbruch, L.; Marinova, M.; Peuckmann‐Post, V.; Rolke, R.
Abstract: Background: This feasibility study addresses the applicability of matrix electrodes for the reduction of ongoing pain in cancer patients via low‐frequency electrical stimulation (LFS). Methods: Low‐frequency matrix stimulation (4 Hz) was applied to the skin within the 'Head's zones' referring to the tumour localization of cancer pain patients. Pain at baseline was compared to a 3‐day treatment interval consisting of 5 min of matrix stimulation in the morning and evening followed by a 3‐day follow‐up period without therapy. Main outcome parameters included numeric rating scale values (rating scale 0–100), painDETECT, HADS, and German pain questionnaire, as well as the opioid intake, calculated as the oral morphine equivalent (OME). Results: Twenty patients with cancer pain (aged 64.4 ± 10.3; 9 women) were examined. In the majority of patients, the pain was classified as nociceptive. The mean pain reduction achieved by matrix therapy was 30%, under stable daily controlled‐release opioid doses between 177 and 184 mg/day (OME). Seventeen patients (85%) were responders, defined by a pain reduction of at least 30%, while four responders experienced a pain reduction of over 50%. The only side effect was short‐term erythema. Conclusion: Findings are consistent with the concept of synaptic long‐term depression in cancer pain induced after conditioning LFS. Despite the short, but well‐tolerated, treatment duration of 2 × 5 min/day, effects persisted throughout the 3‐day follow‐up. Significance: Cutaneous neuromodulation using LFS via a matrix electrode has been shown to be a safe intervention for effectively reducing cancer pain in palliative care patients.